Technical and economic monitoring in semi-intensive dairy sheep farms in the COVAP cooperative (Spain) - Lara P.; Muñoz I.; Gil M.J.; Gómez-Cabrera A.; Beltrán M.; Sánchez M. (Analyse technico-économique des systèmes de production ovine et caprine : méthodologie et valorisation pour le développement et la prospective., 2006)
An emerging system of dairy sheep production in Southern Spain is described through the preliminary results obtained from a questionnaire-based survey answered by members of the COVAP cooperative. The intensification of merino sheep systems and the introduction of high-yielding foreign breeds are the two main practices adopted by the farmers. The technical staff of the cooperative aims to monitor the system in order to steer its development. Certain tools that have been designed for this purpose and the associated problems are also discussed.
Séminaire du sous-réseau Systèmes de Production du réseau Interrégional FAO-CIHEAM de recherche et développement sur les ovins et caprins, 2005/06/16-18, Seville (Spain)